Cultural Diversity Competencies of Managers in the Australian Energy Industry - Dalton, L.; D'Netto, Brian; Bhanugopan, R. (Tennessee State University College of Business, 2015)
Australia has one of the most culturally diverse populations in the world with 27% of the population born outside Australia. This has resulted in increasing diversity in the Australian Energy Industry. Managers within this industry need a much greater level of capability in managing cross culturally. Yet organizations have not focused adequately on developing these diversity management competencies. This study developed an original model called the Diversity Management Competency Model (DMCM) based on a comprehensive review of the literature. The model consists of four quadrants which encompass understanding self, understanding others, workplace analysis and workplace application. The model was used to investigate the extent to which managers in this industry believe they have developed diversity management competencies. The sample consisted of thirty managers from the electricity industry in Victoria (Australia). The sample was obtained through the use of an extensive network of personal contacts and the snowballing process. Every attempt was made to gain participants from across the industry (from generators through to retail distributors of electricity). The participants included functional managers; principally in operations and maintenance and in support functions like procurement, finance and human resources. Some participants were contacted through their employing organization while other participants were contacted directly. A total of thirty managers were interviewed for the research. The managers participated in individual semi structured interviews of approximately thirty minutes. Each interview was conducted on an individual basis, either face to face or via the telephone. The main research question investigated the extent to which managers in the Victorian Energy Industry believe they have developed the competencies identified in the DMCM to effectively manage diversity in the workplace. Analysis of the data indicated that the level of competencies possessed by managers in Quadrant 1 was “Moderate”. Participants were able to provide some examples of the steps they took to improve diversity awareness. They also indicated that they possessed a learning orientation and were able to revise their own strategies to manage diversity. However, the responses indicated that managers had a “Low” level of competencies for the other three quadrants which included understanding others, workplace analysis and workplace application. Participants really struggled to provide examples to support the competencies identified in the last three quadrants. The DMCM can be used to identify competency deficiencies and organizations can provided management development programs to address these deficiencies. In addition, the model can be used as a screening device in the recruitment process.